Anterior Knee Pain reduction by patellar thickness reduction in Total Knee Replacement - Choochat Kantayaporn; Teerachai Puempanich (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2019)
Background: Anterior knee pain(AKP) was a common complication after total knee replacement(TKR). This condition can be occurred in both patellar resurfacing and non-resurfacing technique. An increase in patellar thickness 1 mm or more postoperatively was associated with lower gain in WOMAC score. Objective: To compare AKP and up and down stair function after patellar thickness reduction and patellar non-resurfacing TKR.